Pengaruh Komunikasi, Motivasi, dan Lingkungan Kerja Terhadap Kepuasan Kerja Karyawan Dinas Pemadam Kebakaran Kabupaten Paser - Joharatul Isna; Misna Ariani; Imam Arrywibowo (El-Mal: Jurnal Kajian Ekonomi & Bisnis Islam, 2025)
The purpose of this study was to determine the effect of Communcation, Motivation, and Work Environment on Job Satisfaction of Paser Regency Fire Department Employees. The type of research used is quantitative research. The sampling technique in this study was total / census sampling with a population of 88 employees, so the sample taken was all employees of the Paser Regency Fire Service, totaling 88 employees. The data collection method was carried out by distributing questionnaires. This study uses multiple linear regression with the help of SmartPLS in processing data. The results of this study indicate that communication variables partially affect the job satisfaction of Paser Regency Fire Department employees, motivation variables partially affect the job satisfaction of Paser Regency Fire Department employees, and work environment variables partially affect the job satisfaction of Paser Regency Fire Department employees